Informal Disaster Governance - Patrizia Isabelle Duda; Ilan Kelman; Navonel Glick (Politics and Governance, 2020)
Scholars and practitioners are increasingly questioning formal disaster governance (FDG) approaches as being too rigid, slow, and command-and-control driven. Too often, local realities and non-formal influences are sidelined or ignored to the extent that disaster governance can be harmed through the efforts to impose formal and/or political structures. A contrasting narrative emphasises so-called bottom-up, local, and/or participatory approaches which this article proposes to encapsulate as Informal Disaster Governance (IDG). This article theorises IDG and situates it within the long-standing albeit limited literature on the topic, paying particular attention to the literature’s failure to properly define informal disaster risk reduction and response efforts, to conceptualise their far-reaching extent and consequences, and to consider their ‘dark sides.’ By presenting IDG as a framework, this article restores the conceptual importance and balance of IDG vis-à-vis FDG, paving the way for a better understanding of the ‘complete’ picture of disaster governance. This framework is then considered in a location where IDG might be expected to be more powerful or obvious, namely in a smaller, more isolated, and tightly knit community, characteristics which are stereotypically used to describe island locations. Thus, Svalbard in the Arctic has been chosen as a case study, including its handling of the 2020 Covid-19 pandemic, to explore the merits and challenges with shifting the politics of disaster governance towards IDG.